2022
DOI: 10.3390/ma15062146
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Capacity Fading in High-Voltage NMC Batteries with the Addition of Reduced Graphene Oxide

Abstract: Lithium-ion batteries for electric vehicles (EV) require high energy capacity, reduced weight, extended lifetime and low cost. EV manufacturers are focused on Ni-rich layered oxides because of their promising attributes, which include the ability to operate at a relatively high voltage. However, these cathodes, usually made with nickel–manganese–cobalt (NMC811), typically experience accelerated capacity fading when operating at a high voltage. In this research, reduced graphene oxide (rGO) is added to a NMC811… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Among the Ni-rich cathode family members, LiNi 0.8 Mn 0.1 -Co 0.1 O 2 (NMC811) has become popular. [4][5][6][7][8][9] However, the increased lithium extraction available with increasing Ni content means that degradation due to surface O loss is more pronounced. 10 Namely, the gain in capacity with increased Ni contents comes in detriment of the cycle life with larger cycling voltage windows.…”
Section: Introductionmentioning
confidence: 99%
“…Among the Ni-rich cathode family members, LiNi 0.8 Mn 0.1 -Co 0.1 O 2 (NMC811) has become popular. [4][5][6][7][8][9] However, the increased lithium extraction available with increasing Ni content means that degradation due to surface O loss is more pronounced. 10 Namely, the gain in capacity with increased Ni contents comes in detriment of the cycle life with larger cycling voltage windows.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of composite of NMC-type cathode materials with different graphenes (graphene oxide), their common advantages are higher electronic conductivity and better interfacial charge transfer process. [18][19][20][21]. In addition, graphene performs a protective function slowing the cathode/electrolyte interfacial side reaction both in the system with liquid electrolyte [20] and in the all-solid-state system [21].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, graphene performs a protective function slowing the cathode/electrolyte interfacial side reaction both in the system with liquid electrolyte [20] and in the all-solid-state system [21]. The authors [19] showed that graphene also ensures the mechanical integrity of the NMC electrode by restraining the propagation of microcracks. The same advantages of using graphene materials are characteristic of anodic composites, for example based on TiO 2 [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation peaks around 4.0 V correspond to the transition from M to hexagonal-2 (H2). Then H2 transfers to hexagonal-3 (H3) at around 4.2 V[36,37]. Corresponding reduction peaks during the reverse process are also labeled.…”
mentioning
confidence: 99%